Development, health, and international policy: the research and innovation dimension - Paulo Marchiori Buss; Claudia Chamas; Miriam Faid; Carlos Morel
Abstract: This text main objective is to discuss development and health from the perspective of the influence of global health governance, using as the tracer the dimension of research, development, and innovation policies in health, which relate to both important inputs for the health system, like drugs and medicines, vaccines, diagnostic reagents, and equipment, and innovative concepts and practices for the improvement of health systems and public health. The authors examine the two main macro-processes that influence development and health: the post-2015 Development Agenda and the process under way in the World Health Organization concerning research and development, intellectual property, and access to health inputs. The article concludes, first, that much remains to be done for the Agenda to truly represent a coherent and viable international political pact, and that the two macro-processes related to innovation in health need to be streamlined. But this requires democratization of participation by the main stakeholders - patients and the general population of the poorest countries - since this is the only way to overcome a "zero sum" result in the clash in the current debates among member State representatives.